Criminal justice : - Adler, Freda (McGraw-Hill, 2003)
This full color, paperback text offers a current, lively and thorough introduction to criminal justice covering past developments, contemporary issues, and tomorrow's challenges, and drawing students into the intriguing world of criminal justice. Manageable in terms of size and price, Criminal Justice: An Introduction holds a unique place in the market, offering a portable and affordable alternative to encyclopedic texts, and more complete coverage than brief core texts.